(مدح النبی صلى الله عليه وسلم عندأحمد شوقی (دراسۃ وصفیۃ فنیۃ: AHMAD SHAWKI’S ADMIRATION OF THE PROPHET(PEACE BE UPON HIM): A METHODOLOGICAL STUDY (Zia e Tahqeeq, 2025)
Ahmad Shawqi was one of the renowned religious poets of the Egypt. He earned popularity as a great Arabic poet and play-writer during the twentieth century. He had a great contribution in modern Arabic and Islamic literature. He served as an Islamic Arabic poet .He was born in Egypt. He went abroad to France for higher education. On his return to his country in 1894, he joined nationalist group and resisted British occupation in Egypt. He also became a prominent member of Arab literary culture until the British forced him to exile in southern Spain. He remained in Andalusia during 1914 to 1920. He then returned to Egypt. He was entitled: Amir al-Shuaraa in recognition of his contribution to Arabic literature. This article evaluates Shawqi’s poetry in which he present biography of Holy Prophet (peace be upon him). His poetry shows his love to Islam and the Holy Prophet (peace be upon Him. The article describes his style, literary beauty i.e. terminology, similes, metaphors and illusions.